In vitro modelling of androgen-mediated gene-directed enzyme prodrug therapy for the treatment of prostate cancer - Vajda, Alice (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Radiation Therapy, 2012)
Gene-directed enzyme prodrug therapy has the potential to improve prostate cancer therapy outcome and could be used on its own or as an adjuvant to the current treatments. This research involved the characterisation of a vector previously created in the Prostate Molecular Oncology Research Group, pPPE-CD, in which the promoter and enhancer of prostate specific antigen (PSA) gene had been cloned upstream of the gene for cytosine deaminase (CD). CD is an enzyme that converts a drug with relatively low toxicity, 5-flourocytosine (5-FC) to its active form, 5-flourouracil. This strategy may allow for specific targeting of prostate tumour cells as CD expression is restricted by androgen levels, which bind to the androgen receptor (AR), activating it and upregulating PSA expression.
Keywords: Radiation Therapy, Ph.D.; Ph.D. Trinity College Dublin